Characterization of emeralds by micro‐Raman spectroscopy1. (27th June 2014) - Bersani, Danilo; Azzi, Giulia; Lambruschi, Erica; Barone, Germana; Mazzoleni, Paolo; Raneri, Simona; Longobardo, Ugo; Lottici, Pier Paolo; Ropret, Polonca; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> In recent years, the use of Raman spectroscopy as a gemological tool has largely increased, in particular in the conservation science field where a non‐destructive and contactless identification is required. In this work, we show the large amount of information which is possible to obtain with Raman analysis on one of the most important gems, emerald, the green variety of beryl. In particular, 14 not certified faceted emeralds have been studied by means of a standard micro‐Raman spectrometer, allowing also the identification of some fakes (garnet, glass, and quartz). All the emerald gems have been fully characterized from the vibrational point of view. In particular, the high frequency spectrum, in the OH region, has been exploited to estimate the amount of alkali ions present in the channels of the crystalline structure. In addition, solid and fluid inclusions have been identified and were useful to hypothesize the provenance of the mineral. The shape and position of the characteristic laser‐induced luminescence of chromium ions have helped to better define the origin of the gems. Copyright © 2014 John Wiley & Sons, Ltd.